2013
DOI: 10.3892/br.2013.65
|View full text |Cite
|
Sign up to set email alerts
|

The cytotoxicity of mercury chloride to the keratinocytes is associated with metallothionein expression

Abstract: Abstract. There are trace amounts of heavy metals in cosmetics. Heavy metals such as mercury (Hg), which is added to skin-whitening cosmetics, may cause acute or chronic damage to human cells. The aim of this study was to investigate the cytotoxicity of mercury chloride (HgCl 2 ) to human keratinocytes. The keratinocytes were treated with various concentrations of HgCl 2 and the cell survival fractions were found to be 38.08, 17.59, 12.76, 3.29 and 0.77% when the cells were treated with 0.25, 0.5, 0.75, 1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…To analyse the effectiveness of CI-vesicles containing PG-E with regard to decreasing the damage caused by heavy metals in keratinocytes, different concentrations of lead acetate and mercuric chloride and a mixture of both were applied to HaCaT cells. Individually, both metals caused a reduction in cell viability (data not shown), as reported previously in other studies [67,68], but in this work assays were also carried out with a mixture of lead acetate and mercuric chloride. An important reduction in cell viability was shown after 24 h of incubation of HaCaT cells with different concentrations of the metals and in the same way as previously reported, the reduction being highly dose-dependent [68].…”
Section: Discussionsupporting
confidence: 85%
“…To analyse the effectiveness of CI-vesicles containing PG-E with regard to decreasing the damage caused by heavy metals in keratinocytes, different concentrations of lead acetate and mercuric chloride and a mixture of both were applied to HaCaT cells. Individually, both metals caused a reduction in cell viability (data not shown), as reported previously in other studies [67,68], but in this work assays were also carried out with a mixture of lead acetate and mercuric chloride. An important reduction in cell viability was shown after 24 h of incubation of HaCaT cells with different concentrations of the metals and in the same way as previously reported, the reduction being highly dose-dependent [68].…”
Section: Discussionsupporting
confidence: 85%
“…Several studies have shown that metals such as copper, zinc, and mercury are important inducers of MT synthesis, especially between 6 and 48 h after exposure [38][39][40][41][42][43]. Thus, we believe that the lower Hg content from animals that received Zn-Hg may be related to the synthesis of MT, since these proteins are rich in SH groups that may sequester Hg ions helping in its elimination.…”
Section: Discussionmentioning
confidence: 84%
“…Its toxicological innocuousness has to be evaluated as well. Tests can be performed on artificial skin, but skin cell viability tests, e.g., cytotoxicity assays, are usually performed on human keratinocytes or melanocytes [183][184][185]. Skin By comparison, even fewer EOs/hydrosols (1.8%) display some whitening potency (no inhibition higher than 20%).…”
Section: Further Development Of a Cosmetic Ingredientmentioning
confidence: 99%
“…Its toxicological innocuousness has to be evaluated as well. Tests can be performed on artificial skin, but skin cell viability tests, e.g., cytotoxicity assays, are usually performed on human keratinocytes or melanocytes [183][184][185]. Skin irritancy testing is usually performed on human keratinocytes [186]; human repeat insult patch testing (HRIPT, repeated applications of products on the skin, under an occlusive patch, in healthy adult volunteers) has also been developed to assess the dermal irritation or sensitization potency of a molecule.…”
Section: Further Development Of a Cosmetic Ingredientmentioning
confidence: 99%